Case Report: Duodenal gastrointestinal stromal tumor misdiagnosed as tumor located on the major duodenal papilla leading to fatal gastrointestinal bleeding in a child - Yang, Chengxian; Li, Kewei; Xiang, Bo (Frontiers in Pediatrics, 2025)
BackgroundAlthough gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract, they are rare in children, particularly those located on the duodenum. Here, we present an interesting pediatric case involving a 13-year-old boy who experienced gastrointestinal hemorrhage, he was misdiagnosed with a tumor located on the major duodenal papilla and was ultimately confirmed to be duodenal GISTs.Case presentationA 13-year-old boy presented to a local hospital with fatigue and melena. Gastroscopy suggested a tumor located at the major duodenal papilla, and the patient was referred to our hospital for surgical evaluation. Upon further investigation and surgical exploration, the diagnosis was revised to a duodenal GIST with surface ulceration and active bleeding. The ulcer's morphology and location mimicked the appearance of the major duodenal papilla, leading to the initial diagnostic error.ConclusionsDuodenal GISTs in pediatric patients often present asymptomatically but can manifest with severe complications such as fatal gastrointestinal bleeding. The tumor's morphology and location can obscure the major papilla, complicating preoperative diagnosis and influencing surgical decision-making. Comprehensive preoperative evaluation and careful intraoperative exploration are critical for accurate diagnosis and optimal management.